An uncorrelated relaxed-clock analysis suggests an earlier origin for flowering plants - Smith, Stephen A. (National Academy of Sciences, 2010)
We present molecular dating analyses for land plants that incorporate 33 fossil calibrations, permit rates of molecular evolution to be uncorrelated across the tree, and take into account uncertainties in phylogenetic relationships and the fossil record. We attached a prior probability to each fossil-based minimum age, and explored the effects of relying on the first appearance of tricolpate pollen grains as a lower bound for the age of eudicots. Many of our divergence-time estimates for major clades coincide well with both the known fossil record and with previous estimates. However, our estimates for the origin of crown-clade angiosperms, which center on the Late Triassic, are considerably older than the unequivocal fossil record of flowering plants or than the molecular dates presented in recent studies. Nevertheless, we argue that our older estimates should be taken into account in studying the causes and consequences of the angiosperm radiation in relation to other major events, including the diversification of holometabolous insects. Although the methods used here do help to correct for lineage-specific heterogeneity in rates of molecular evolution (associated, for example, with evolutionary shifts in life history), we remain concerned that some such effects (e.g., the early radiation of herbaceous clades within angiosperms) may still be biasing our inferences.